Carcass and Tibia Bone of Broiler Chickens Fed Amorphophallus companulatus tubers Fermented by Bacillus subtilis - Theresia Nur Indah Koni; Zuprizal; Rusman; Chusnul Hanim (Faculty of Animal Science, Universitas Brawijaya, 2022)
The objective of the present study was to investigate the effect of fermented Amorphophalllus companulatus (AC) tubers by Bacillus subtilis on the final weight, carcass weight, and tibia bone of broiler chickens. The feeding trial lasted for 35 days. One hundred and twelve eight days old male broilers of the New Lohmann strain were used for the study. There were four treatment groups and four replications with seven birds per replicate. The four treatments were 1) a control diet without FAC, 2) a diet with 5% FAC, 3) a diet with 10% FAC, and 4) a diet with 15% FAC. The variable observed were final weight, carcass weight, abdominal fat weight, percentage of carcass weight, length, and weight of tibia bone. The result showed that feeding FAC tubers meal did not affect (P>0.05) final weight, carcass weight, the percentage of carcass weight, length, and weight of tibia bone. Feeding FAC tuber meal up to 15% had lower (P<0.05) abdominal fat than feeding control dietary. In conclusion, fermented AC by Bacillus subtilis can be used up to 15% in broiler diets without adversely affecting carcass weight and tibia bone.